Imperial powers and democratic imaginations - Slater, David (Sociedad y Economía, 2007)
The analytical nucleus of this paper is formed through a consideration of some primaryaspects of the interconnections between a resurgent imperialism and a contestad terrain ofdemocratic politics. There are three sections: in the first part an exploratory examination ofsignificant elements of the contemporary literature on imperialism is developed, and thisincludes a discussion of the relationality of imperial power, the differentiation of imperialityfrom imperialism and the neglected importance of the agents of imperialist power. The secondsection attempts to tease out some of the specificities of the United States as an imperialdemocracy set within a broad context of North-South relations. This leads into a finaldiscussion of the geopolitics of democratization. The paper is an exploratory treatment ofcertain features of an extensive conceptual and political terrain formed by the intersectionsbetween imperialism and democratic politics.